Distinct Effects of Nalmefene on Dopamine Uptake Rates and Kappa Opioid Receptor Activity in the Nucleus Accumbens Following Chronic Intermittent Ethanol Exposure - Rose, Jamie H. (Int J Mol Sci, 2016)
The development of pharmacotherapeutics that reduce relapse to alcohol drinking in patients with alcohol dependence is of considerable research interest. Preclinical data support a role for nucleus accumbens (NAc) κ opioid receptors (KOR) in chronic intermittent ethanol (CIE) exposure-induced increases in ethanol intake. Nalmefene, a high-affinity KOR partial agonist, reduces drinking in at-risk patients and relapse drinking in rodents, potentially due to its effects on NAc KORs. However, the effects of nalmefene on accumbal dopamine transmission and KOR function are poorly understood. We investigated the effects of nalmefene on dopamine transmission and KORs using fast scan cyclic voltammetry in NAc brain slices from male C57BL/6J mice following five weeks of CIE or air exposure. Nalmefene concentration-dependently reduced dopamine release similarly in air and CIE groups, suggesting that dynorphin tone may not be present in brain slices. Further, nalmefene attenuated dopamine uptake rates to a greater extent in brain slices from CIE-exposed mice, suggesting that dopamine transporter-KOR interactions may be fundamentally altered following CIE. Additionally, nalmefene reversed the dopamine-decreasing effects of a maximal concentration of a KOR agonist selectively in brain slices of CIE-exposed mice. It is possible that nalmefene may attenuate withdrawal-induced increases in ethanol consumption by modulation of dopamine transmission through KORs.